SPIRITUALITY AND ITS RELATIONSHIP WITH THE QUALITY OF LIFE IN A STUDENT OF MEDICINE (CIPEEX, 2022)
SPIRITUALITY AS SOMETHING THAT TRANSCENDS THE PHYSICAL, LINKED TO THE SACRED AND THE SEARCH FOR ANSWERS ABOUT THE MEANING OF LIFE, HAS BEEN REPORTED AS AN IMPORTANT FACTOR TO FACE SITUATIONS OF HUMAN VULNERABILITY AND AS A FACTOR OF RESILIENCE, AS WELL AS PHYSICAL AND PSYCHIC RECOVERY OF PATIENTS. INCREASED SENSE OF PURPOSE IN LIFE IS EFFECTIVE IN PROVIDING REFERRAL FOR STRESSFUL CONDITIONS SUCH AS ILLNESS AND SITUATIONS THAT REQUIRE DEDICATION TO HELP ONESELF AND OTHERS. THE PURPOSE OF THIS STUDY IS TO EVALUATE THE INFLUENCE OF SPIRITUALITY ON THE HEALTH AND WELL-BEING OF MEDICAL GRADUATES, WHO ARE GRADUATING IN A PROFESSION THAT DEMANDS CONFRONTATION WITH LIFE AND DEATH ISSUES IN THE DOCTOR-PATIENT RELATIONSHIP, AS WELL AS SITUATIONS STRESSORS THAT REQUIRE HIGH EFFORT AND PERSONAL CAPACITY. THE EVALUATION WILL BE MADE THROUGH A QUALITATIVE-QUANTITATIVE CROSS-SECTIONAL STUDY, WHERE EMPATHY, SPIRITUALITY / RELIGIOSITY / PERSONAL BELIEFS AND QUALITY OF LIFE AND SOCIODEMOGRAPHIC PROFILE WILL BE APPLIED. IT IS HOPED TO FIND A RELATIONSHIP BETWEEN THE QUALITY OF LIFE OF MEDICAL STUDENTS AND SPIRITUALITY / RELIGIOSITY.
Keywords: Spirituality. Health. Medical students. Quality of life.